Analisis Postur Kerja Pembuatan Rokok PT Wan Tobacco Cigarette Dengan Metode Standard Nordic Questionnaire (SNQ) Dan Rapid Entire Body Assessment (REBA) - Ahmah Jainul Firdaus; Akmal Suryadi (International Forum of Researchers and Lecturers, 2023)
This study analyzes work posture in cigarette manufacturing at PT Wan Tobacco Cigarette using the Standard Nordic Questionnaire (SNQ) and Rapid Entire Body Assessment (REBA) methods. Manual handling work has the potential to cause health risks due to physical loads and non-ergonomic postures. PT Wan Tobacco Cigarette faces problems with ergonomic risky work activities, especially in the cigarette manufacturing machine section, with worker complaints such as muscle fatigue and health problems in the hands, upper arms, back and neck. The SNQ method is used to identify complaints on the employee's body parts, while the REBA method is used to analyze work posture as a whole. This study focuses on assessing work posture when transferring tobacco to cigarette making machines. The REBA method was chosen because of the complexity and dynamics of employee activities. This research is expected to contribute to improving workers' posture to make it more ergonomic and help PT Wan Tobacco Cigarette control the risk of health problems caused by ergonomic factors. By identifying work posture problems and employee complaints, companies can implement changes in the design of work methods and work stations that are more ergonomic to improve worker comfort and welfare.